Kafa’ah in Contemporary Muslim Women’s Perspective: Selectivity in Partner Choice amid Reverse Gender Inequality - Khoiriyah Dwi Safitri; Martoyo Martoyo; Abdul Wahab (Al-Qalam Institue, 2026)
This study examines the concept of kafa’ah from the perspective of contemporary Muslim women as a basis for selectivity in partner selection amid the phenomenon of reverse gender inequality. In contemporary social contexts, women are no longer positioned merely as objects within marital relations, but as active subjects possessing autonomy in determining their life partners. The growing discourse surrounding the perception that “marriage is scary” has further reinforced women’s selective attitudes toward marriage institutions. This research employs a qualitative method with an empirical socio-legal approach. Data are collected through literature review and are intended to be complemented by in-depth interviews with women aged 20–40 years who possess higher educational backgrounds. The data are analyzed using thematic analysis. Preliminary findings indicate that the concept of kafa’ah has undergone a significant transformation, shifting from a normative understanding of compatibility based on social status toward broader dimensions of equality, including shared values, life vision, emotional maturity, and psychological readiness. Contemporary Muslim women experience substantial social changes that influence their expectations and considerations in choosing a partner. The study concludes that kafa’ah in contemporary Muslim women’s perspectives is no longer limited to social equivalence, but increasingly emphasizes value alignment, emotional compatibility, and mutual readiness as essential foundations for marital relationships.